O comentário crítico em relatórios de observação de aulas: contributos para uma reflexão sobre a profissionalidade docente - Duarte, Isabel Margarida (2016)
At present, when considering models for initial teachers training the capacity toreflect on different aspects of teaching is valued. The efficiency of the approaches used to developthis capacity in the students is an open question. Knowledge about the results of the tools usedin initial teachers training may be enhanced by the analysis of one of the texts types where thereflexion is transcribed, the classroom observation report.The section of the classroom observation report centred in the critical comment is the objectof study. Hence, the analysis looks at the linguistic and pragmatics description of the utteranceswhere the critical reflection takes form. The results show a discursive organisation with a strong investment in movements of justification/explanation and repair, accordingly to the principles of courtesy/politeness in speech (Fonseca 1996), and in strategies of attenuation commonly present in the utterances of the discursive segment under analysis (Briz 2007), namely the assertive and appreciative ones.Data is relevant for the regulation of formation processes leading to the development of critical thinking and reflection about classroom practice for future teachers.